Periodic coordination in hierarchical air defence systems - Arabas, Piotr; Malinowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
The subject of this work is the defence planning of a point target against an air attack. The defence system is decomposed into a number of sectors. A direct method of coordination is used at the upper level, while the sectors use a discrete-time event-based model and the description of uncertainty by multiple scenarios of an attack. The resulting problems are solved using linear programming. A comparison of two coordination strategies for realistic attack scenarios and an analysis of effectiveness are provided.
Keywords: Missile Defence; hierarchical systems; coordination; decision support systems